2021
DOI: 10.3390/jtaer16070155
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Game Analysis of Blockchain Technology Preventing Supply Chain Financial Risks

Abstract: Because of the risks existing in supply chain finance, taking accounts receivable factoring business as the research object, this paper uses the evolutionary game method to analyzes the factors affecting the decision-making of the participants in supply chain finance, constructs an evolutionary game model between small and medium-sized enterprises and financial institutions, and analyzes the mechanism of blockchain to solve the financial risks of the supply chain by comparing the changes of evolutionary stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…Temperature is crucial to the quality and safety of fresh agricultural products in the cold chain, and for perishable products, real-time temperature information can be translated into a prediction of their remaining shelf-life, which can then be used to improve supply chain management [ 12 ]. In recent years, artificial neural networks have been gradually applied in the shelf-life prediction of aquatic products [ 13 ]. The advantage of artificial neural networks is that they can synthesize multiple indicators without considering the relationship between parameters to reduce systematic errors, and they improve the accuracy of prediction through continuous learning.…”
Section: Related Workmentioning
confidence: 99%
“…Temperature is crucial to the quality and safety of fresh agricultural products in the cold chain, and for perishable products, real-time temperature information can be translated into a prediction of their remaining shelf-life, which can then be used to improve supply chain management [ 12 ]. In recent years, artificial neural networks have been gradually applied in the shelf-life prediction of aquatic products [ 13 ]. The advantage of artificial neural networks is that they can synthesize multiple indicators without considering the relationship between parameters to reduce systematic errors, and they improve the accuracy of prediction through continuous learning.…”
Section: Related Workmentioning
confidence: 99%
“…(2) Set up a special repayment account to supervise the repayment capital flow of the core enterprise. In the supply chain finance accounts receivable pledge financing business, the general loan contract will require the core enterprise to repay the accounts receivable into the account designated by the bank to serve the sub-business (He et al, 2021). So they have to bank for small and medium-sized enterprises with the core enterprises of both sides payment account of regulation, to be specified in the provisions in the contract to the outside of the core enterprise accounts for payment, otherwise the payment behavior invalid provision, and clearly told that the two sides, with the person this, prevent malicious fraud, reduce the probability of joint fraud for alpha, ensure the business smoothly.…”
Section: Strengthen Supervision Over Small and Medium-sized Enterprisesmentioning
confidence: 99%
“…However, Chinese smes still face many obstacles in their development process, the most important of which is the difficulty of financing. The financing problem of small and medium-sized enterprises has become the biggest obstacle to their sustainable and stable development and industrial transformation and upgrading (Sun, He & Su, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2022) and Zheng et al (2022) designed a blockchain‐based financial data management model and an enterprise information sharing model, respectively, to achieve credit information exchange in the supply chain investigation system. Sun et al (2021) constructed a two‐party accounts receivable evolutionary game model of the SME and the financial institution, and calculated the change scenarios of evolutionary stabilization strategies before and after applying blockchain technology, which is found to effectively mitigate the operational risk of financial institutions by maintaining credit defaults in a high‐risk state. Su et al (2022) analyzed the impact of blockchain technology on the stability strategies of a tripartite evolutionary game with financial institutions, core firms, and SMEs, and found that increases in the amount of default losses and receivables can reduce the default probability.…”
Section: Introductionmentioning
confidence: 99%
“…Although Wang et al (2019) and Lin and Peng (2021) examined this issue and emphasized on the illegal financing access of SMEs, the notion that a majority of supply chain finance risk exposure arises from the embezzlement of loans by financing firms and the operational risks of unauthorized discharge of pledge by supporting enterprises has been ignored. Sun et al (2021) and Su et al (2022) analyzed the role of blockchain on accounts receivable financing, but the features of the role of blockchain technology in inventory pledge financing require separate research since great differences exist in involved subjects and financing approaches. Considering that the inactivity of financial institutions may induce violations of logistics enterprises and SMEs, their excessive control will incur a reduction in profits.…”
mentioning
confidence: 99%